Financial Therapy: Theory, Research, and Practice - Klontz, Bradley T (Springer, 2015)
Money-related stress dates as far back as concepts of money itself. Formerly it may have waxed and waned in tune with the economy, but today more individuals are experiencing financial mental anguish and self-destructive behavior regardless of bull or bear markets, recessions or boom periods. From a fringe area of psychology, financial therapy has emerged to meet increasingly salient concerns.